Organizational Behavior Management in Creating Competent Human Resources - Syah, Rizky Herdian (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research aims to analyze employment planning in the school environment, including analysis of activities and workload, as well as evaluation of recruitment, selection, training and development of teaching staff. Research background shows that good workforce planning can improve school efficiency and effectiveness. The research method used is analysis of activity and workload data, as well as evaluation of teacher recruitment, selection, training and development. The research results show that workforce planning is more focused on academic and non-academic aspects in recruitment and selection, with less emphasis on behavior change through training. Evaluations are carried out periodically, but there are gaps in program progress and implementation. The implications of these findings indicate the need for increased focus on aspects of behavior change in teacher training and development programs as well as improvements in the assessment and implementation of employment evaluations in schools.